Implementación de un sistema de abrevadero para ganado vacuno en las fincas Abigail y la Envidia en la parroquia Guasaganda. - Celi Gómez, Xavier Eduardo (2022)
The present research consists of the implementation of an automated system of troughs for the hydration of cattle in the Abigail and Envidia farms in Guasaganda, whose problem was evidenced in the lack of technicality regarding the care of ruminants where they lacked troughs and filling system, which caused the cattle to be put at risk due to lack of hydration or, in the second case, mortality caused by accidents. For this, the measurement of the flow was initially carried out, how far away it was, where the intake would be to transfer the water, on the way it was possible to observe the overflows that are more frequent in winter since it is located 300m at the foot of the mountain. This measurement allowed an estimate to be made of the flow travel time. Volumetric measurement was used to obtain data on the speed of the water and how long it arrived. In addition, the estimation of the amount of water that cattle need was made, where weight and environmental temperature were taken into account. For the design of the troughs, the CAD Inventor software was used, later, based on the designed model, the troughs were built with specific measures according to the demand of the ruminants. Once the troughs were ready, the automatic system was implemented in a PVC box, assembling and placing the selected devices of electronic components for local use, properly programmed and electrically adequate for the purpose of automation, which is designed automatically. to send a signal from an Arduino board to the sensors and the solenoid valve so that it fulfills its functions of opening and closing the filling of the troughs. The result obtained was the automatic handling of the filling system with management based on experience, which allows the system to work autonomously.